2021
DOI: 10.3389/fonc.2021.775136
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Reconstruction of a Large Maxillary Defect With an Engineered, Vascularized, Prefabricated Bone Graft

Abstract: The reconstruction of complex midface defects is a challenging clinical scenario considering the high anatomical, functional, and aesthetic requirements. In this study, we proposed a surgical treatment to achieve improved oral rehabilitation and anatomical and functional reconstruction of a complex defect of the maxilla with a vascularized, engineered composite graft. The patient was a 39-year-old female, postoperative after left hemimaxillectomy for ameloblastic carcinoma in 2010 and tumor-free at the 5-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…It can also be used as a source of bone graft. A recent case report confirmed the clinical translation capacity of in vivo osteo-organoid strategy in addressing large maxillary defect ( 24 ). We have previously confirmed that the bone morphogenetic protein–2 (BMP-2)–loaded scaffold–induced in vivo osteo-organoid at different developmental stages could serve as a robust osteogenic tissue for critical bone defect repair ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 71%
“…It can also be used as a source of bone graft. A recent case report confirmed the clinical translation capacity of in vivo osteo-organoid strategy in addressing large maxillary defect ( 24 ). We have previously confirmed that the bone morphogenetic protein–2 (BMP-2)–loaded scaffold–induced in vivo osteo-organoid at different developmental stages could serve as a robust osteogenic tissue for critical bone defect repair ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 71%
“…Bone from allogeneic donors is gamma irradiated or freeze-dried to eliminate the cellular components and pathogenic agents, thus reducing their immunogenicity. 14 Allografts are osteoconductive and retain at least partly their osteoinductivity depending on the decellularization process. Although allografts are also histocompatible, they exhibit a higher failure rate compared to autografts.…”
Section: Therapeutic Alternatives For Critical-size Bone Defects In T...mentioning
confidence: 99%
“…Bone tissue from living or cadaveric human donors constitutes the allografts. Bone from allogeneic donors is gamma irradiated or freeze-dried to eliminate the cellular components and pathogenic agents, thus reducing their immunogenicity . Allografts are osteoconductive and retain at least partly their osteoinductivity depending on the decellularization process.…”
Section: Therapeutic Alternatives For Critical-size Bone Defects In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to regenerate bone gives the surgeon another avenue to reconstruct the patient to normalcy without donor site morbidity [ 70 ]. To address instances where the soft tissue condition is suboptimal or a soft tissue defect is present after the excision of a malignant tumor, a combination of tissue-engineered bone with radial forearm flap and latissimus dorsi flap has been reported by Schlund et al [ 71 ] and Ismail et al [ 77 ], respectively. ( Figure 3 ) Soft tissue engineering was also applied to fabricate keratinized oral mucosal grafts which were pre-laminated to a fibula flap for later jaw reconstruction [ 78 ].…”
Section: Future Perspectivesmentioning
confidence: 99%